2020
DOI: 10.3390/pathogens9080651
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Contamination of Dental Unit Waterlines and Potential Risk of Infection: A Narrative Review

Abstract: Several studies have revealed that dental unit waterlines (DUWLs) are often contaminated by large numbers of various micro-organisms (bacteria, fungi, protozoa, viruses). Microbial contamination in DUWLs may originate from the mains water piped into the dental unit, the suck-back of patients’ saliva into the line due to the lack of adequate valves, and contamination from bottled water systems. Some of the main determinants of microbial contamination in DUWLs are: a very small lumen size (0.5–2 mm) of the tubin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 62 publications
1
30
0
3
Order By: Relevance
“…It is estimated that most Pseudomonas water system contamination is confined to the distal 2 m of the water system [34]. P. aeruginosa is among the species frequently found in dental unit waterlines [5,[35][36][37], where it is capable of forming biofilms on the inner surface of narrow-bore plastic tubing that carries water to the high-speed handpiece, air/water syringe and ultrasonic scaler. A very small lumen size (0.5-2 mm), high surface to volume ratio (6:1), low throughput, the materials of which the tubing is made and water stagnation in DUWL, when units are not in use, further encourages biofilm growth [36].…”
Section: Pseudomonas Aeruginosa Reservoirs In Healthcare Settingmentioning
confidence: 99%
“…It is estimated that most Pseudomonas water system contamination is confined to the distal 2 m of the water system [34]. P. aeruginosa is among the species frequently found in dental unit waterlines [5,[35][36][37], where it is capable of forming biofilms on the inner surface of narrow-bore plastic tubing that carries water to the high-speed handpiece, air/water syringe and ultrasonic scaler. A very small lumen size (0.5-2 mm), high surface to volume ratio (6:1), low throughput, the materials of which the tubing is made and water stagnation in DUWL, when units are not in use, further encourages biofilm growth [36].…”
Section: Pseudomonas Aeruginosa Reservoirs In Healthcare Settingmentioning
confidence: 99%
“…Different potential environmental reservoirs of this micro-organism have been described in healthcare settings (aerosols, taps, basin and shower drains, respiratory equipment, humidifiers, endoscopes and endoscope washers, hydrotherapy pools, dental units, etc.) [ 11 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A lot of human commensal bacteria of the skin such as Micrococcus spp., S. epidermidis and S. hominis were identified in the air and on the surfaces sampled. In some dental consulting rooms, bacteria such as Pseudomonas aeruginosa and Stenotrophomonas maltophilia were identified: these bacteria may originate from the water of the dental units [ 21 , 22 ]. In this study, no oral bacteria originated from the dental plaque were identified, but they may be found in dental consulting rooms [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the micro-organisms indoor originated from two main sources: the outdoor air and the anthropogenic sources such as people from their skin, their clothing, and their respiratory systems [ 23 , 24 ]. They can also originate from healthcare activities or from other environmental sources such as water, notably in dental consulting rooms which are largely contaminated by aerosols or spatters containing micro-organisms originate from the dental unit [ 22 ].…”
Section: Discussionmentioning
confidence: 99%